THE ROLE OF THE NURSE IN THE NON-PHARMACOLOGICAL MANAGEMENT OF PEDIATRIC PAIN: PLAYFUL STRATEGIES AND HUMANIZATION - Gomes, Barbara Santana; Carvalho, Beatriz Nogueira Barbosa; Azzolin, Gabriela Carmo Marchiori; Fernandes, Maísa Axcar; Marques, Maria Luísa Sousa Severo; Randi, Yara Maria (Editora Impacto Científico, 2025)
Pediatric pain is a complex phenomenon influenced by physiological, emotional, and sociocultural factors and remains underestimated in several healthcare settings. This study aimed to analyze scientific evidence regarding pain assessment in children, hospital humanization strategies, and non-pharmacological interventions used in pediatric pain management. An integrative literature review was conducted in the SciELO, BVS, and PePSIC databases between September and October 2025, using controlled descriptors in Portuguese and English. Original articles published between 1993 and 2025 involving children aged 0 to 12 years in hospital or outpatient settings were included. After applying the eligibility criteria, 20 studies composed the final sample. Results show that pain assessment should consider the child’s developmental stage, with behavioral scales recommended for neonates (PIPP, N-PASS, COMFORT) and tools such as FLACC, FPS-R, and Wong-Baker for preverbal and older children. Non-pharmacological interventions demonstrated significant effectiveness, especially the use of sucrose and non-nutritive sucking in neonates, as well as audiovisual distraction, storytelling, guided breathing, and desensitizing devices (such as Buzzy® and Pikluc®) in older children. Hospital humanization strategies—including playrooms, therapeutic play, psychological support, and active family participation—were shown to reduce anxiety, improve adaptation, and strengthen the therapeutic bond. It is concluded that pediatric pain management requires a multidisciplinary, systematic, and child-centered approach, integrating appropriate assessment, non-pharmacological interventions, and humanized care practices. Incorporating these strategies into institutional protocols may improve care quality, reduce traumatic experiences, and promote greater comfort and safety for children and their families. DOI: https://doi.org/10.56238/edimpacto2025.078-001